2022
DOI: 10.1002/jper.21-0608
|View full text |Cite
|
Sign up to set email alerts
|

Association between groups of immunoglobulin G antibodies against periodontal microorganisms and diabetes‐related mortality

Abstract: Background: Immunoglobulin G (IgG) antibodies against periodontal microorganisms can be markers of periodontal infection because their levels rise following infection and remain elevated several years later. Methods:We evaluated the relationship between groups of IgG antibodies against 19 periodontal microorganisms and diabetes-related mortality over 27 years among participants of the National Health and Nutrition Examination Survey III (1988 to 1992) aged ≥40 years at the time of examination (N = 8,153). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A number of studies have assayed circulating IgG antibodies to periodontal bacteria using various techniques, such as checkerboard immunoblotting, dot blotting, and enzyme-linked immunosorbent assay, to examine the association between IgG antibodies to periodontal pathogens and risk of coronary artery disease ( 18 ), atherosclerosis and hypertension ( 19 ), diabetes ( 20 ), rheumatoid arthritis ( 21 ), chronic kidney disease ( 22 ), and Alzheimer disease ( 23 ). A history of periodontitis as well as the presence of circulating IgG antibodies to key periodontal pathogens have been associated with increased risk for various types of cancers, including pancreatic, oropharyngeal, esophageal, and colorectal cancers ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have assayed circulating IgG antibodies to periodontal bacteria using various techniques, such as checkerboard immunoblotting, dot blotting, and enzyme-linked immunosorbent assay, to examine the association between IgG antibodies to periodontal pathogens and risk of coronary artery disease ( 18 ), atherosclerosis and hypertension ( 19 ), diabetes ( 20 ), rheumatoid arthritis ( 21 ), chronic kidney disease ( 22 ), and Alzheimer disease ( 23 ). A history of periodontitis as well as the presence of circulating IgG antibodies to key periodontal pathogens have been associated with increased risk for various types of cancers, including pancreatic, oropharyngeal, esophageal, and colorectal cancers ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…But a bidirectional mendelian randomization study invovled 117386 European patients showed that PD is not the cause of AD development [32] . And a crosssectional study showed that clusters of IgG antibodies against periodontal microorganisms did not predict AD mortality [33] . In general, the general trend of most studies investigating the cross-sectional or longitudinal association between PD and AD suggests that there is a positive correlation between these two disease processes.…”
Section: The Correlation Between Pd and Admentioning
confidence: 99%
“…Bacteremia due to periodontal pathogens induce multipotent progenitors such as myeloid potential and granulocyte-macrophage progenitors, which promotes inflammation in other organs [10]. Oral inflammation has a deteriorative effect on several organ systems and increases the risk of developing systemic diseases, such as diabetes [11][12][13], cardiovascular diseases [14], low-weight birth [15], atherosclerosis [16], amyotrophic lateral sclerosis [17], and respiratory tract infection [18]. A previous case-control study demonstrated that people suffering from periodontitis had a three times higher risk for the development of hospital-acquired pneumonia compared with inpatients without periodontitis [19].…”
Section: Introductionmentioning
confidence: 99%